Chiral Sensing Using Circularly Polarized Luminescence of Bis(phenanthroline dicarboxylic acid) EuIII Complex Induced by Allosteric‐type Interaction with Amino Acid Molecules. Issue 4 (23rd January 2019) - Iwamura, Munetaka; Fujii, Mai; Yamada, Ayano; Koike, Hikaru; Nozaki, Koichi
Abstract: [Eu(pda)2 ] − and [Eu(bda)2 ] − (pda=1, 10‐phenanthroline‐2, 9‐dicarboxylic acid; bda=2, 2′ bipyridine 5, 5′‐dicarboxylic acid) have an achiral D 2 d structure in crystals. These complexes exhibit circularly polarized luminescence (CPL) in water containing chiral amino acids. In this work, induced CPL of [Eu(pda)2 ] − and [Eu(bda)2 ] − in water solutions containing a mixture ofd ‐ andl ‐ amino acids were examined. Plots of g lum values of the induced CPL as a function of mol‐fraction ofl ‐ andd ‐ arginine reveal that [Eu(pda)2 ] − favors homo‐association ([Eu(pda)2 ] − ‐(l ‐arginine)2 or [Eu(pda)2 ] − ‐(d ‐arginine)2 ) over hetero‐association {[Eu(pda)2 ] − ‐(l ‐arginine)⋅(d ‐arginine)}. This suggests that association of an arginine molecule induces a structural change in [Eu(pda)2 ] − to promote chiral selective association to another arginine, i.e., homo‐allosteric association. On the other hand, the system of [Eu(pda)2 ] − with histidine favors hetero‐allosteric association over homo‐association. No allosteric effect is recognized in CPL from [Eu(bda)2 ] − . Abstract : Thinking in a circular way : Circularly polarized luminescence (CPL) is exhibited from achiral Eu III complexes such as [Eu(phenanthroline‐2, 9‐dicarboxylic acid)2 ] − in water containing chiral amino acids. CPL as a function of mole‐fractions ofd ‐ andl ‐amino acids revealed that association of chiral amino acid molecules induces structural changes in the Eu III complexes to chiral structures which promote chiral selective associations to other amino acid molecules.